Blood Pressure Response and Pulse Arrival Time During Exercise Testing in Well-Trained Individuals - Heimark, Sondre; Eitzen, Ingrid; Vianello, Isabella; Bøtker-Rasmussen, Kasper G.; Mamen, Asgeir; Hoel Rindal, Ole Marius; Waldum-Grevbo, Bård; Sandbakk, Øyvind; Seeberg, Trine M. (Frontiers in Physiology, 2022)
Introduction: There is a lack of data describing the blood pressure response (BPR) in well- trained individuals. In addition, continuous bio-signal measurements are increasingly investigated to overcome limitations of intermittent cuff-based BP measurements during exercise testing. Thus, the aim of the present study was to assess the BPR in well-trained individuals during a cycle ergometer test with particular focus on the systolic BP (SBP), and to investigate pulse arrival time (PAT) as a continuous surrogate for SBP during exercise testing. Materials and Methods: Eighteen well-trained male cyclists were included (32.4 ± 9.4 years; maximal oxygen uptake was 63 ± 10 ml/min/kg) and performed a stepwise lactate threshold test with 5-minute stages, followed by a continuous test to voluntary exhaustion with 1-min increments when cycling on an ergometer. BP was measured with a standard automated exercise BP cuff. PAT was measured continuously with a non-invasive physiological measurements device (IsenseU) and metabolic consumption was measured continuously during both tests. Results: At lactate threshold (281 ± 56 W) and maximal intensity test (403 ± 61 W), SBP increased from resting values of 136 ± 9 mmHg to maximal values of 219 ± 21 mmHg and 231 ± 18 mmHg, respectively. Linear within-participant regression lines between PAT and SBP showed a mean r2 of 0.81 ± 17. Conclusions: In the present study focusing on the BPR in well-trained individuals, we observed a more exaggerated systolic BPR than in comparable recent studies. Future research should follow up these findings to clarify the clinical implications of the high BPR in well-trained individuals. In addition, PAT showed strong intra-individual associations, indicating a potential use as a surrogate SBP measurement during exercise testing.